Integrated transcriptomics and metabolomics reveal key metabolic pathway responses in Pistia stratiotes under Cd stress - Wei, Zhao; Zhongbing, Chen; Xiuqin, Yang; Luying, Sheng; Huan, Mao; Sixi, Zhu (Journal of hazardous materials, 2023)
Cadmium (Cd) can interfere with plant gene expression, change the content of metabolites and affect plant growth. In this study, untargeted metabolomics (LC-MS) and RNA-Seq sequencing were performed on root tissues of Pistia stratiotes exposed to Cd stress. The results showed that cadmium stress affected the accumulation and transport of cadmium in plants and increased the content of soluble sugar, the activities of ascorbate peroxidase (APX), and peroxidase (POD) by 34.89%, 41.45%, and 6.71% on average, and decreased the activity of superoxide dismutase (SOD) by 51.51% on average. At the same time, the contents of carotenoid, chlorophyll a, and chlorophyll b decreased by 29.52%, 20.11%, and 13.14%, respectively, Thus affecting the growth and development of plants. Metabolomic analysis showed that Cd stress affected eight metabolic pathways, involving 27 differentially expressed metabolites, mainly including unsaturated fatty acids, amino acids (phenylalanine), nucleotides, sulfur compounds, and flavonoids. By transcriptome analysis, a total of 3107 differentially expressed genes (DEGs, 2666 up-regulated genes, and 441 down-regulated genes) were identified, which were mainly involved in four pathways, among which glutathione metabolism and lignin biosynthesis were the key metabolic pathways. In conclusion, this study reveals the metabolic and transcriptional response mechanisms of P. stratiotes to Cd stress through multi-omics, providing the theoretical basis for the phytoremediation of water contaminated by Cd.
Keywords: Araceae; kořeny rostlin; Cd stress; Metabolome; Cadmium; stanovení celkové genové exprese; kadmium; Chlorophyll A; Gene Expression Profiling; Metabolic Networks and Pathways; Pistia stratiotes; metabolické sítě a dráhy; Plant Roots; Phytoremediation; Transcriptome; chlorofyl a; transkriptom